Corporate social responsibility in global supply chains of multinational companies - Holger Görg; Aoife Hanley; Adnan Seric (Kiel Institute for the World Economy (IfW), 2015)
This paper looks at the importance of CSR considerations in the decision taken by a foreign affiliate of a multinational company about the choice of local suppliers. We investigate this empirically using unique firm level data for more than 2,000 foreign owned firms in 19 Sub-Saharan African countries. In terms of the role of global value chains we find that firms that import intermediates from their parent company abroad are more likely to implement CSR. Similarly, CSR plays a larger role for affiliates that export their output to developed countries. This suggests that the immediacy of the production chain provides a strong link to CSR: Intermediate inputs are imported from HQ and are then processed, together with locally sourced inputs, into a final good, which is then exported for consumption in developed countries. Furthermore, our results show that the determinants of environmental and social CSR activities are likely to be different.
Keywords: F23; M14; O14; 330; corporate social responsibilities; global supply chains; multinational companies